Over-expression of Activated Signal Transducer and Activator of Transcription 3 Predicts Poor Prognosis in Upper Tract Urothelial Carcinoma - Li, Wei-Ming (Int J Med Sci, 2017)
Background: Signal transducer and activator of transcription proteins (STATs) play important roles in gene regulation, cell proliferation, and cell differentiation. We aimed to establish the relationship between phosphorylated STAT3 (p-Ser-STAT3) expression and the prognosis of upper tract urothelial carcinoma (UTUC). Methods: This study retrospectively reviewed 100 patients with pathologically confirmed UTUC at Kaohsiung Medical University Hospital. We quantified the expression of p-Ser-STAT3 in cancer cells by immunohistochemistry, and determined the clinicopathological significance of p-Ser-STAT3 expression and prognostic outcomes in patients with UTUC. Results: High p-Ser-STAT3 expression was detected in 52% of UTUC patients. High p-Ser-STAT3 expression was associated with poor recurrence-free survival (p = 0.018) and overall survival (p = 0.026). In advanced cancer samples (stage T3/T4), p-Ser-STAT3 expression is the only independent prognostic factor for recurrence-free survival (hazard ratio = 5.91, p = 0.01) and cancer-specific survival (hazard ratio = 8.83, p = 0.039). Conclusions: The expression of p-Ser-STAT3 can be a potential prognostic marker for cancer recurrence and survival in UTUC, especially in advanced stage cases.